Right Ventricle to Left Ventricle ratio at CTPA predicts mortality in Interstitial Lung Disease - Bax, Simon (Chest, 2020)
INTRODUCTION: Patients with interstitial lung disease (ILD) may develop pulmonary hypertension (PH), often disproportionate to ILD severity. Right ventricle to left ventricle diameter ratio (RV:LV) measured at CT pulmonary angiography (CTPA), has been shown to provide valuable information in pulmonary arterial hypertension patients and to predict death or deterioration in acute pulmonary embolism. METHODS: Demographics, ILD subtype, echocardiography and detailed CTPA measurements were collected in consecutive patients undergoing both CTPA and right heart catheterisation (RHC) at the Royal Brompton Hospital between 2005 and 2015. Fibrosis severity was formally scored using CT criteria. RV:LV ratio at CTPA was evaluated by three different methods. Cox-proportional hazard analysis was used to assess the relation of CTPA-derived parameters to predict death or lung transplantation. RESULTS: 92 patients were included: 64% male, mean age 65±11 years, with FVC 57±20% (predicted), TLCO(c) 22±8% (predicted) and KCO(c) 51±17% (predicted). PH was confirmed at RHC in 78%. Of all CTPA-derived measures, an RV:LV ratio ≥1.0 strongly predicted mortality or transplantation at univariate analysis (HR 3.26, 95%CI:1.49-7.13, p=0.003), whereas invasive haemodynamic data did not. The RV:LV ratio remained an independent predictor at multivariate analysis (HR: 3.19, CI:1.44-7.10, p=0.004), adjusting for an ILD diagnosis of IPF and CT derived ILD severity. CONCLUSION: An increased RV:LV ratio measured at CTPA provides a simple, non-invasive method of risk stratification in patients with suspected ILD-PH. This should prompt closer follow up, more aggressive treatment and consideration of lung transplantation.